2022
DOI: 10.2196/37016
|View full text |Cite
|
Sign up to set email alerts
|

Underestimated Prevalence of HIV, Hepatitis B Virus (HBV), and Hepatitis D Virus (HDV) Triple Infection Globally: Systematic Review and Meta-analysis

Abstract: Background Hepatitis delta virus (HDV) is a satellite RNA virus that relies on hepatitis B virus (HBV) for transmission. HIV/HBV/HDV coinfection or triple infection is common and has a worse prognosis than monoinfection. Objective We aimed to reveal the epidemiological characteristics of HIV/HBV/HDV triple infection in the global population. Methods A systematic literature search in PubMed, Embase, and the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
(44 reference statements)
1
7
0
Order By: Relevance
“…Out of the 7 patients who were HIV/HBsAg coinfected, 6 (6.4%) tested positive to the HDV antigen. This result is within the range of result reported by Opaleye et al [17] with a 5.6% prevalence of the HDV antigen among HIV/HBV co-infected individuals but slightly lower than the global prevalence of 7.4% recorded from the findings of Chen et al [18]. This could be due to the higher global prevalence of HIV/HBV as reported by Ahmadi Gharaei et al [15], since the hepatitis B surface antigen(HbsAg) is required for the defective HDV to replicate as discovered by Coghill et al [1].…”
Section: Discussionsupporting
confidence: 87%
“…Out of the 7 patients who were HIV/HBsAg coinfected, 6 (6.4%) tested positive to the HDV antigen. This result is within the range of result reported by Opaleye et al [17] with a 5.6% prevalence of the HDV antigen among HIV/HBV co-infected individuals but slightly lower than the global prevalence of 7.4% recorded from the findings of Chen et al [18]. This could be due to the higher global prevalence of HIV/HBV as reported by Ahmadi Gharaei et al [15], since the hepatitis B surface antigen(HbsAg) is required for the defective HDV to replicate as discovered by Coghill et al [1].…”
Section: Discussionsupporting
confidence: 87%
“…But a recent study looking at viral loads of HBV and HDV from patients with HBV‐A, ‐D, and ‐E genotypes showed the greatest impacts on HBV‐A, suggesting genotypic differences in vulnerability to suppression 28 . Similarly, in the case of triple infection (HIV‐HDV‐HBV), HIV can also influence the viral loads of the others 28,29 . In our review, we identified 21 cases of HIV‐HBV‐HDV infection, wherein only five had paired genotyping but without a clear trend (Table S1b).…”
Section: Discussionmentioning
confidence: 94%
“…28 Similarly, in the case of triple infection (HIV-HDV-HBV), HIV can also influence the viral loads of the others. 28,29 In our review, we identified 21 cases of HIV-HBV-HDV infection, wherein only five had paired genotyping but without a clear trend (Table S1b). For some studies, genotyping both viruses was either not the priority and/or perhaps from a region with well-known HBV or HDV genotypes regionally that they were inferred for their study.…”
Section: Hdv-1 Genotypes (Largely Hdv-2 and 4)mentioning
confidence: 99%
“…Moreover, indications have claimed an underestimation of the prevalence of HBV infection 6 . HBV infection would increase the risk of co‐infection with other infectious viruses like hepatitis C virus, hepatitis D virus, or human immunodeficiency virus 6–8 …”
Section: Introductionmentioning
confidence: 99%